The failure of the Muslim league in post-colonial Pakistan: a critical appraisal - Sheikh, Irfan Ahmed; Arshad Islam, Islam; Jatoi, Bashir Ahed; Ahmed Khan, Shafique (2018)
Significance: Nations states in developing societies were a legacy of colonial rule. The catastrophic world wars of the European metropolis had spillover effects in developing countries, where colonialism was replaced by communism and nationalism among post-colonial peoples. The political parties who led anticolonial nationalist movements employed demonstrations, agitation, and mobilization at broader level for their intentions, but without the existential enemy of the colonial oppressor they were prone to division and faced numerous incidentals, natural and hostile challenges, particularly in the case of Pakistan, whose birth was deliberately sabotaged by British imperialism as well as Indian nationalism. Nevertheless, the Muslim League was essentially successful in its fundamental aim of creating a Muslim state in South Asia and began to administer it after independence. This study explores the character and role played by the post-colonial political parties, especially the Muslim League, whose consequences left the effects on dictatorship generally and on politics particularly that have shaped the development of South and Central Asia ever since.